Fifty years of BMT: risk stratification, donor matching, and stem cell collection for transplantation - Salhotra, Amandeep; Yuan, Shan; Ali, Haris (Frontiers in Oncology, 2023)
In this review, we discuss recipient risk assessment for allo-HCT regarding comorbidities present at baseline to predict non relapse mortality. We further reviewed the incorporation of remission status and cytogenetic risk prior to allograft transplantation to predict relapse rates for hematologic malignancies. HCT-CI and DRI are tools available to physicians to assess the risk–benefit of allo-HCT in patients referred for transplantation. Next, we discuss our algorithm for donor selection and criteria for donor selection in case matched donors are not available. Finally, we discuss our approach for stem cell mobilization, especially in donors failing G-CSF, and our approach for the use of plerixafor and data supporting its use.